Beyond physical ability—predicting women’s football performance from psychological factors - Pettersen, Susann Dahl; Martinussen, Monica; Handegård, Bjørn Helge; Rasmussen, Lene-Mari Potulski; Koposov, Roman; Adolfsen, Frode (Frontiers in Psychology, 2023)
Introduction Even though there is a clear agreement among researchers that psychological factors are a vital part of a football player’s performance, the topic has not been investigated thoroughly. The present study aimed to examine the predictive value of psychological factors on female football players’ match performance. Methods A sample of 156 players from the top two leagues in Norway completed the following questionnaires: Perceived Motivational Climate in Sport Questionnaire 2 (PMCSQ-2), Big Five Inventory (BFI-20), Self-Regulated Learning questionnaire, and Grit-S and Sport Mental Toughness Questionnaire (SMTQ). Match performance data were collected from the online database of the performance analysis company InStat. Results Results from a linear mixed model analysis showed that perceived mastery climate and extraversion were the only significant predictors of performance. Other relevant indicators, such as mental toughness, self-regulated learning, and grit, did not predict performance. Discussion These findings suggest that the team climate facilitated by coaches may be more important for predicting match performance than individual psychological factors.